Pengembangan Model Sistem Pembelajaran Berbasis Komputer (SPBK) Pada Mata Kuliah Pengantar Ilmu Komputer Di Universitas Negeri Makassar - Ummiyat Rahmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
his study is research and development which aims at developing a computer- based instruction model for the course Introduction to Computer Science. The objective is translated into specific one, namely to get the implementation form of Introduction to Computer Science course that was held at the Department of Electronics Engineering Education an PTIK FT-UNM. In addition, it was also to develop the concepts, the procedures, as well as to find out the results of the development of Computer-Based Instruction (CBI) for effective and efficient Introduction to Computer Science for the Students of Electronics Engineering Education Department, PTIK FT UNM. The results showed that experts’ assessment for the material got 91.79%, a media / programming was 94.52% and design experts was 89.44% in a very good category. Furthermore, the assessment of effectiveness and practicality stated that the product were well-developed, fit to use, and very helpful in learning activities.